PENGARUH JARAK TANAM DAN FREKUENSI PENYIANGAN TERHADAP PERTUMBUHAN, HASIL KACANG TANAH (Arachis hypogaea L ) DAN POPULASI GULMA - Dina Yulianti Sisca Vera; Edhi Turmudi; Eko Suprijono (Jurnal Ilmu-Ilmu Pertanian Indonesia, 2020)
[THE EFFECT OF PLANTING DISTANCE AND WEDDING FREQUENCY ON GROWTH, YIELD OF PEANUT (Arachis hypogaea L) AND WEED POPULATION]. This study was aimed to determine planting distance and frequency of weeding which gives the highest growth and yield of peanuts. Peanut plants were planted in the Experimental Field of the Faculty of Agriculture, Bengkulu University from October to December 2018. The study was arranged in a Complete Randomized Block Design (RCBD) with 2 factors and 3 replications. The first factor is the planting distance of 40 cm x 20 cm; 40 cm x 30 cm and 40 cm x 40 cm. The second factor is the frequency of weeding consisting of no weeding, 1x weeding (age 2 WAP), 2x weeding (2 and 4 WAP), and 3x weeding (2, 4, and 6 WAP). The results showed that the interaction between the spacing of 40 cm x 40 cm and 2 x weeding can increase plant height. The spacing of 40 cm x 40 cm can reduce the population and dry weight of broadleaf weeds. The planting distance of 40 cm x 30 cm can increase the fresh weight of pods, pod weight/plot, and the highest dry weight of pods/plants. The frequency of weeding 2x can reduce the population and dry weight of broadleaf weeds; whereas weeding frequency 3x can reduce weed populations of grass and sedges- weeds, and dry weight of broadleaf weeds. The 3x weeding frequency can also increase the total number of pods/plants, pod weight/plot, and pod weight/plant.